The Controversy over Salt Intake - Vinall, Maria (MD Conference Express, 2014)
In 1980, the recommendation from the Dietary Guidelines for Americans was to “avoid too much sodium.” Over time, however, formal guidelines have set ever-lowering intake goals, for which the scientific basis has become a matter of debate. Offering new snew perspectives on this controversy, this article discusses how dietary reference intakes are set, the relationship between sodium intake and cardiovascular disease, as well as population nutrition trends.